Desire for Independence and Financial Status as Determinants of Entrepreneurial Intention among National Diploma Students in Taxation in North-Eastern Nigeria - Umar, J. M.; Bappah, A. S. (Kashere Journal of Education, 2021)
This study Desire for Independence and financial status as Determinants of Entrepreneurial Intention among National Diploma students in Taxation in North-Eastern Nigeria. The purpose of the study was to determine the entrepreneurial intention among National Diploma students in business studies in North-Eastern Nigeria. The study was guided by two objectives, with corresponding research questions and null hypotheses. Relevant literature related to the study was reviewed. The design for the study was descriptive survey. The population of the study comprised 24,625 National Diploma II students of Schools of Business studies of all the Polytechnics in North-Eastern Nigeria. The researcher sampled 379 subjects using proportionate random sampling technique. The instrument for data collection was developed by the researcher through adaptation from the existing instruments. The instrument was validated by 4 experts. The instrument was tested and reliability coefficient of 0.80 was obtained. The research questions were answered using descriptive statistics (mean and standard deviation) while the hypotheses were tested using regression analysis. The study revealed that Desire for independence; has large extent influence on students’ entrepreneurial intention. Financial status also has large extent influence on students’ entrepreneurial intention of National Diploma students in business studies in North-Eastern, Nigeria. Based on the results, it was recommended, that the students should be encouraged to embrace entrepreneurship education or training in order for them to become self-reliant and wealth creators; The Government should make accessible loans available for graduates of the National Diploma in business studies so as to start up their businesses.